Use of Gentamicin in the Isolation of Subgroup A Chlamydia - Wentworth, Berttina B. (Antimicrob Agents Chemother, 1973)
The use of gentamicin to control contamination in a tissue culture system for the isolation of Chlamydia was investigated. Gentamicin, at concentrations up to 100 μg/ml, did not appear to inhibit the growth of stock chlamydial strains, as judged by assays for iodine-staining inclusions. When 343 cervical and urethral specimens were examined in the presence and in the absence of gentamicin, significantly more isolations of chlamydiae were obtained in the presence of 10 μg of gentamicin/ml, and significantly fewer unsatisfactory results due to contaminating organisms were seen. Therefore, this aminoglycoside antibiotic appears to be a useful addition to a cell system for isolation of Chlamydia.